2011
DOI: 10.1007/s10534-011-9486-6
|View full text |Cite
|
Sign up to set email alerts
|

As2O3 oxidation by vitamin C: cell culture studies

Abstract: The ability of As(2)O(3) to induce apoptosis in various malignant cell lines has made it a potential treatment agent for several malignancies. In this study the chemical stability of As(2)O(3) (As(III)) in cell-free growth media with various compositions was studied (MEM with different amount of amino acids and DMEM). Special attention was given to evaluate the influence of serum (FBS; fetal bovine serum) absence and vitamin C addition on the oxidation of As(III) to As(V) in cell-free growth media. FBS is an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Arsenite is thought to induce ROS through activation of NADPH oxidase (Nox) isoforms as well as through the mitochondria (28, 29) and can produce both superoxide as well as hydrogen peroxide in the cytoplasm. Arsenite is stable in serum-containing media over long periods unlike exogenously added hydrogen peroxide (30, 31) and has been reported to induce checkpoint responses mediated by caffeine-sensitive protein kinases (26). As expected, ATM depletion resulted in a complete defect in the phosphorylation of known ATM substrates including KAP1 and CHK2 after each treatment we used (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Arsenite is thought to induce ROS through activation of NADPH oxidase (Nox) isoforms as well as through the mitochondria (28, 29) and can produce both superoxide as well as hydrogen peroxide in the cytoplasm. Arsenite is stable in serum-containing media over long periods unlike exogenously added hydrogen peroxide (30, 31) and has been reported to induce checkpoint responses mediated by caffeine-sensitive protein kinases (26). As expected, ATM depletion resulted in a complete defect in the phosphorylation of known ATM substrates including KAP1 and CHK2 after each treatment we used (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the use of common exogenous antioxidants such as resveratrol can indirectly attenuate As 2 O 3 -induced hepatoxicity by increasing antioxidant enzyme activities and GSH/GSSG ratio or through direct chelation in the case of α-lipoic acid to reduce As 2 O 3 -induced cardiotoxicity . However, studies in cell-free growth media show vitamin C to be prooxidative by increasing the rate of As III oxidation to As V , while in rats vitamin E showed a protective effect by reducing DNA damage and the TNF-α level, and inhibiting caspase cascade activation . In consideration of recent studies that link arsenic exposure to oxidative stress and ROS generation, our findings further show that organic arsenicals generate various ROS when exposed to common oxidants in solution.…”
Section: Discussionmentioning
confidence: 99%
“…In general, basic cell growth media are deficient in antioxidants. The amount of ROS produced during growth in culture medium depends not only on the cell type but also on the composition of the medium and whether the culture is incubated in light or (to a lesser extent) in the dark 41 – 43 . The buffering capacity and composition of the medium are important with regard to the behavior of the cultured cells and may affect significantly the results 44 .…”
Section: Cell Culturementioning
confidence: 99%
“…The buffering capacity and composition of the medium are important with regard to the behavior of the cultured cells and may affect significantly the results 44 . In fact, it has been suggested that cell studies using different cell growth media are scarcely comparable 43 .…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation